Technical services & consultancy UMP - UMP, PNC (Penerbit UMP, 2010)
UMP-Industry Synergy- To fulfill its ambition to become a world-class university, University Malaysia Pahang (UMP) has, on many occasions, collaborated with the local industries, to propagate higher technical productivity. Several industrial-related and relevant programmes, including technical services, were coordinated by the university's wholly-owned subsidiary, UMP Holdings Sdn Bhd. Listed below are the services and facilities offered by UMP to the local industries.